2015
DOI: 10.5958/0974-0279.2016.00012.4
|View full text |Cite
|
Sign up to set email alerts
|

Crop Diversification towards High-value Crops in India: A State Level Empirical Analysis

Abstract: The paper has examined state-level trends and patterns in crop diversification in India for the period 1990-91 to 2011-12 using Simpson Index of Diversification (SID) and panel regression analysis. The study has revealed that cropping pattern at state level is transforming from foodgrains to high-value crops but the transformation is not uniform across the states/regions. The values of SID have confirmed that the agricultural economy has diversified in all the states with some fluctuations in case of food crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 2 publications
2
13
0
Order By: Relevance
“…This means, higher cropping intensity is confined to monocropping in coastal Odisha where irrigation intensity is relatively higher, whereas it is associated with multicropping practice in rainfed districts of western and southern Odisha. However, the finding of this paper supports the view of Kumar and Gupta (2015b) that cropping intensity has significant positive impact on crop diversification as farmers have inclination to rotate the crops for maintaining soil fertility through nutrient recycle. Table 15 also gives another interesting observation that there exists a very high degree of correlation (0.629) between irin and hyv.…”
Section: Discussionsupporting
confidence: 73%
“…This means, higher cropping intensity is confined to monocropping in coastal Odisha where irrigation intensity is relatively higher, whereas it is associated with multicropping practice in rainfed districts of western and southern Odisha. However, the finding of this paper supports the view of Kumar and Gupta (2015b) that cropping intensity has significant positive impact on crop diversification as farmers have inclination to rotate the crops for maintaining soil fertility through nutrient recycle. Table 15 also gives another interesting observation that there exists a very high degree of correlation (0.629) between irin and hyv.…”
Section: Discussionsupporting
confidence: 73%
“…Conversely, Punjab, and Haryana were found to have low Simpson Index value, i.e. nearly 0.70 or below for recent past years indicating low level of overall agricultural diversification which is consistent with previous studies (Kumar and Gupta, 2015;Singh et al, 2006). However Rajasthan, Jammu & Kashmir, Bihar, Jharkhand, Chhattisgarh, Uttar Pradesh, Himachal Pradesh, Uttarakhand, and Madhya Pradesh have depicted a moderate level of agricultural diversification with SID value ranging from 0.71 to 0.80.…”
Section: Spatio Temporal Trend and Agricultural Diversification Statusupporting
confidence: 90%
“…Variable Selection: The exogenous variables incorporated in the empirical model were selected following existing literature on agricultural diversification (Kumar and Gupta, 2015; 2007; Singh et al, 2006) and on relationship between farm income and agricultural diversification (Birthal et al, 2015;Bravo-Ureta et al, 2006). Table 1 portrays the description of variables included in the empirical model.…”
Section: Empirical Econometric Modelmentioning
confidence: 99%
“…In this study both production and consumption diversity have been estimated. The production diversification studies have mostly used Simpson (Kumar and Gupta, 2015), Herfindhal, Entrophy, Shannon and Margalef diversity index measures. We have adopted Simpson index of diversification for our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Family farming played a key role in securing food and nutrition security in India (Singh et al, 2014), however, in recent years market-driven agriculture has made a significant impact on food consumption pattern of rural households, and urbanization and rising income levels have changed consumption habits of urban households. The studies on agriculture focused on production pattern, crop diversification and their determinants (Chand, 1996;Joshi et al, 2003;Kumar and Gupta, 2015) and nutrition have emphasized on the consumption of calories, micro and macro nutrients intake and importance of diversified food consumption for better health (Drescher et al, 2007;Lumole, 2013;Viswanathan et al, 2015). A recent study has identified various linkages and pathways between agriculture and * Author for correspondence nutritional outcome in South Asia (Pandey et al, 2016).…”
Section: Introductionmentioning
confidence: 99%